TREATMENT OF GROUND WATER CONTAMINATED OIL DERIVATIVES - Velimir Šćekić; Radoje Cvejić; Sava Smiljić (Journal of Engineering & Processing Management, 2014)
Treatment of groundwater is the most important part of the scope of protection of natural resources, because no biological and bacteriological water there is no life on the planet. Implemented through consideration of all the negative elements in the water, determine the percentage of their toxicity and finding the most appropriate method for their removal. The aim is to monitor, improve water quality and the environment in general observed.
Keywords: oil; petroleum